O adolescente em conflito com a lei: que acesso tem ele às políticas públicas? um recorte na cidade de São Paulo - Cividanes, Natália Lôbo Oliveira (2015)
This work address the subject related to the adolescents in conflict with the law, discussing the paths they followed in the course of their lives, and the (in) possibility of public policies became a mediator in this experience. In the Brazilian history it was appointed that children and adolescents have acquired and showing visibility in a slow process, which placed them as subject to the interests of the bourgeoisie. With the new Federal Constitution of 1988 and the Statute of Children and Adolescents, moves the way to see them, which become a priority target in the implementation of policies designed in order to protect them, prioritizing their own interests in preference to any other. For the adolescent, who is assigned the execution of an offense, is given a new look in the direction of educating, seeking their reintegration into society through a policy of inclusion and service, acting for their welfare, intending to she never again recur, and is entered in education, training and the labor market. The research that supports this work shows that the State not only fails to help and support these young people, as at times even contribute to the perpetuation of a life marked by violence, been it compulsory, before or after the fulfillment of socio-educational measures. This research investigates the stories of adolescents who have been through the deprivation of liberty and opens an opportunity for them to say their understanding of the world and their access to public policies, especially in education, health, courses, assistance and justice. The results provide important elements for discussion about the act of offending and the history of this offense, from the hardships reports of these adolescents have spent in the course of their lives, both of material goods, such as immaterial. We completed the survey of the thematic reduction of legal age, an issue not only current, but also representative of the largest Brazilian setback as the rights not only of teenagers but of an entire nation